2019
DOI: 10.1097/md.0000000000014421
|View full text |Cite
|
Sign up to set email alerts
|

Association between food allergy and ankylosing spondylitis

Abstract: Food allergies can alter the gut microbiome composition, increasing the risk of conditions such as ankylosing spondylitis (AS). To identify the association between specific allergens and AS, we investigated the differences in the serum levels of 14 food antigen-specific immunoglobulin (Ig) G between AS patients and healthy participants. The association between the levels of these antibodies and disease activity was assessed by measuring the inflammatory marker C-reactive protein (CRP). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As disease activity varies substantially with AS, an interaction between poor diet and inflammation of the gastrointestinal tract may correlate with severe disease activity (Hascelik et al., 2009). In support, observational research highlighted that patients with AS had higher levels of pork‐specific immunoglobulins than healthy controls, and this was positively associated with CRP concentrations (Niu et al., 2019). However, as with PA studies, the cross‐sectional nature of much of the research into diet modification in patients with AS does not allow determination of cause and effect.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…As disease activity varies substantially with AS, an interaction between poor diet and inflammation of the gastrointestinal tract may correlate with severe disease activity (Hascelik et al., 2009). In support, observational research highlighted that patients with AS had higher levels of pork‐specific immunoglobulins than healthy controls, and this was positively associated with CRP concentrations (Niu et al., 2019). However, as with PA studies, the cross‐sectional nature of much of the research into diet modification in patients with AS does not allow determination of cause and effect.…”
Section: Methodsmentioning
confidence: 96%
“…In support, observational research highlighted that patients with AS had higher levels of pork-specific immunoglobulins than healthy controls, and this was positively associated with CRP concentrations (Niu et al, 2019) A high omega-3 fatty acid diet compared to one that was low (4.55 vs. 1.95 g omega-3/day for ∼ 5 months) was significantly more effective at improving BASDAI, but this study was potentially confounded by age, symptom duration, and disease duration, all of which were higher in the low omega-3 dose group (Sundström et al, 2006). Two studies found no significant effect of probiotics on patient reported outcome measures.…”
Section: Dietmentioning
confidence: 92%
“…Because of the evidence, this diet seems promising as a possible strategy for addressing AS. In addition, α-Gal, a food allergen, is the leading natural antigen in mammalian red meat and may be involved in the pathogenesis of AS ( 212 ). On this account, allergenic foods such as beef, crab, and pork should be excluded from the daily diet of AS patients.…”
Section: Targeted Gut Microbiota Therapy In Preventing or Treating Asmentioning
confidence: 99%